CultuSTEM: A Culture-Based Pedagogical Model for Fostering Creativity in Secondary STEM Classrooms - Iis Sugandhi; Evelyn Wang; Firzan Dahlan (Enigma in Education, 2025)
This study investigated the effectiveness of CultuSTEM, a culture-based pedagogical model integrating local culinary heritage with STEM education, in fostering creativity among secondary school students. A quasi-experimental pretest-posttest control group design was employed with 136 Grade 10 students (68 experimental, 68 control) from two public secondary schools in Palembang, Indonesia. The experimental group participated in a 10-week CultuSTEM intervention comprising five thematic modules—fermentation science, thermal dynamics in traditional cooking, spice preservation chemistry, recipe scaling mathematics, and cooking tool engineering—each delivered through a four-phase instructional cycle: Cultural Immersion, Scientific Inquiry, Creative Challenge, and Reflective Synthesis. The Creative Thinking Skills Test, adapted from the Torrance Tests of Creative Thinking, served as the primary outcome measure. MANOVA results revealed a significant multivariate effect (Pillai’s V = 0.412, F(3,132) = 30.84, p < 0.001). ANCOVA analyses, with Bonferroni correction, confirmed that the experimental group significantly outperformed the control group on creative thinking (F(1,133) = 142.68, p < 0.001, partial η² = 0.518), STEM achievement (F(1,133) = 78.42, p < 0.001, partial η² = 0.371), and cultural appreciation (F(1,133) = 45.86, p < 0.001, partial η² = 0.256). Hedges’ g effect sizes ranged from 0.76 to 1.31 across outcome variables, indicating large practical significance. These findings suggest that culturally grounded STEM instruction can substantially enhance creative thinking while simultaneously improving academic performance and cultural engagement.